A 600 kyr reconstruction of deep Arctic seawater δ18O from benthic foraminiferal δ18O and ostracode Mg ∕ Ca paleothermometry - J. R. Farmer; J. R. Farmer; J. R. Farmer; K. J. Keller; K. J. Keller; R. K. Poirier; G. S. Dwyer; M. F. Schaller; H. K. Coxall; H. K. Coxall; M. O'Regan; M. O'Regan; et al. (Climate of the Past, 2023)
The oxygen isotopic composition of benthic foraminiferal tests (δ18Ob) is one of the pre-eminent tools for correlating marine sediments and interpreting past terrestrial ice volume and deep-ocean temperatures. Despite the prevalence of δ18Ob applications to marine sediment cores over the Quaternary, its use is limited in the Arctic Ocean because of low benthic foraminiferal abundances, challenges with constructing independent sediment core age models, and an apparent muted amplitude of Arctic δ18Ob variability compared to open-ocean records. Here we evaluate the controls on Arctic δ18Ob by using ostracode Mg/Ca<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="37pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1e3d1d11bbe5435973a8908703b160da"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-19-555-2023-ie00003.svg" width="37pt" height="14pt" src="cp-19-555-2023-ie00003.png"/></svg:svg> paleothermometry to generate a composite record of the δ18O of seawater (δ18Osw) from 12 sediment cores in the intermediate to deep Arctic Ocean (700–2700 m) that covers the last 600 kyr based on biostratigraphy and orbitally tuned age models. Results show that Arctic δ18Ob was generally higher than open-ocean δ18Ob during interglacials but was generally equivalent to global reference records during glacial periods. The reduced glacial–interglacial Arctic δ18Ob range resulted in part from the opposing effect of temperature, with intermediate to deep Arctic warming during glacials counteracting the whole-ocean δ18Osw increase from expanded terrestrial ice sheets. After removing the temperature effect from δ18Ob, we find that the intermediate to deep Arctic experienced large (≥1 ‰) variations in local δ18Osw, with generally higher local δ18Osw during interglacials and lower δ18Osw during glacials. Both the magnitude and timing of low local δ18Osw intervals are inconsistent with the recent proposal of freshwater intervals in the Arctic Ocean during past glaciations. Instead, we suggest that lower local δ18Osw in the intermediate to deep Arctic Ocean during glaciations reflected weaker upper-ocean stratification and more efficient transport of low-δ18Osw Arctic surface waters to depth by mixing and/or brine rejection.